Correlation Between \(^137Cs\) and \(^40K\) Concentration in Soil and Tea Tree in Luong My Farm, Hoa Binh Province, Vietnam - Duc, Hoang Huu; Cuong, Phan Viet; Loat, Bui Van; Anh, Le Tuan; Minh, Nguyen Dang; Khiem, Le Hong (Communications in Physics, 2019)
In this work, the correlation between 137Cs and 40K concentration in tea tree and soil in Luong My farm, Tan Thanh district, Luong Son commune, Hoa Binh province was experimentally investigated. The measurements were carried out using gamma spectroscopy with high purity germanium detector HPGe. The results showed that 40K is uniformly distributed in the soil depth while 137Cs is mainly located in 10 cm of the soil surface. Soil-plant transfer factor (TF) for 40K varies in the range of 0.491 to 0.623 and that of 137Cs is in range of 0.384 to 0.510. The concentration of these two radionuclides in tree parts is opposite to each other, while 40K is concentrated in the leave, 137Cs is mainly found in the root.